2020
DOI: 10.1007/s00894-020-04536-9
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical characterization of the shikimate 5-dehydrogenase reaction from Mycobacterium tuberculosis by hybrid QC/MM simulations and quantum chemical descriptors

Abstract: In this study, we have investigated the enzyme shikimate 5-dehydrogenase from the causative agent of tuberculosis, Mycobacterium tuberculosis. We have employed a mixture of computational techniques, including molecular dynamics, hybrid quantum chemical/molecular mechanical potentials, relaxed surface scans, quantum chemical descriptors and freeenergy simulations, to elucidate the enzyme's reaction pathway. Overall, we find a two-step mechanism, with a single transition state, that proceeds by an energetically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In this work, we also showed that the correct computation of the descriptors requires a window of MOs around the HOMO–LUMO gap, instead of only the frontier orbitals . Also, in another two of our research group’s works, the reactivity descriptors properly adjusted for macromolecules were capable of theoretically characterizing steps in the catalytic mechanisms of some enzymes. , …”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…In this work, we also showed that the correct computation of the descriptors requires a window of MOs around the HOMO–LUMO gap, instead of only the frontier orbitals . Also, in another two of our research group’s works, the reactivity descriptors properly adjusted for macromolecules were capable of theoretically characterizing steps in the catalytic mechanisms of some enzymes. , …”
Section: Introductionmentioning
confidence: 73%
“…4 Also, in another two of our research group's works, the reactivity descriptors properly adjusted for macromolecules were capable of theoretically characterizing steps in the catalytic mechanisms of some enzymes. 5,6 Despite such advances, the popular postprocessing computational chemistry programs are not suited for calculation of the electronic structure of macromolecules. UCA-Fukui is a specialized software for calculating common CDFT descriptors, 7 but it is limited to parse outputs of the GAUSSIAN package and has not been tested for large molecules.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The f – defined in eq is the sum of the squared ν atomic orbital (AO) coefficients that comprise the HOMO and belong to the k th atom, plus the sum of the product between the coefficients of indices ν, μ, and the corresponding overlap matrix element S μν . An equivalent definition for the f + is presented in eq , using the LUMO instead of the HOMO. In this study, the overall effects tallied in these two Fukui functions were used in combination via the average Fukui function, defined in eq . These quantum chemical descriptors have been identified as useful for determining the toxicity and biological activity of several potential ligands. , For the enzymes, these descriptors have been used to determine reactivity sites, as score functions in molecular docking, and to search protein native structures and find key structures in reaction path simulations. , …”
Section: Reactivity Descriptor Calculationsmentioning
confidence: 99%
“…Recently, our research group showed how simple modifications in the Fukui functions allow their applications, using low-cost semiempirical Hamiltonians, to study polypeptides and protein-ligand binding processes [26]. In addition, our group has showcased these capabilities by making successful applications such as theoretical characterization and profiling of the catalytic cycles of enzymes [27], description of the reactivity of active sites and prediction of their amino-acid residue roles [23,28], the impact of electronic structure variation in the reactivity of the SARS-CoV-I and SARS-CoV-II main proteases in different conformations [29] and rationalization of the effects of Ricin Toxin A chain inhibitors [30].…”
Section: Introductionmentioning
confidence: 99%